Paghublag kag impormasyon! Alta presyon sumpungon!. - Berlin, Nelissa Marie; Chua, Enrique III.; Taal Group (Miag-ao, Iloilo University of the Philippines in the Visayas, College of Arts and Sciences, 2008)
Hypertension is a condition wherein there is too much force exerted by the blood against the arterial wall which can lead to heart or kidney failure, atherosclerosis, and stroke. There are two kinds of hypertension, one is essential hypertension wherein no known cause can be attributed to the development of the condition. The other is called secondary hypertension wherein the ailment is due to a pre-existing condition such as kidney problem, hormonal treatment or presence of tumors. Hypertension is most of the time asymptomatic through some complications such as stroke, renal diseases and heart attacks occur. Several factors attribute to the development of this condition. These are obesity, excessive alcohol intake, family history of high blood pressure, high salt intake, aging, sedentary lifestyle, stress, low potassium intake, low calcium intake, and resistance to insulin. Hypertension can be prevented by controlling most of these factors.
Report (Undergraduate, Bachelor of Science in Public Health) College of Arts and Sciences, University of the Philippines, Miagao, Iloilo.
Keywords: Hypertension